SELF-REGULATION STRATEGIES USED IN A PRACTICUM COURSE: A STUDY OF MOTIVATION AND TEACHING SELF -EFFICACY - Orhan, Feza (HACETTEPE UNIV, 2008)
This study was designed to explore pre-service computer teachers' perception of motivation and response to an instruction based on self-regulated learning strategies. A pre-experimental method was used in this research. Data were collected through the Motivated Strategies for Learning Questionnaire developed by Pintrich and others (1993) and the Teacher Self-efficacy Scale developed by Akkoyunlu and others (2005). Frequency, percentage distribution, t- test analysis were used in analyzing data. During the semester, self-regulated strategies were integrated into the Teaching Practice Course. As a result of this study, after the one semester course, students perceive themselves as being more motivated on the course as well as perceiving a higher level of teacher self-efficacy as a computer teacher. This study was an initial step in encouraging students to develop self-regulatory strategies like planning, organizing, monitoring and evaluating their own work. The results provide a reference for instructors that they can embed self-regulatory strategies into their courses.
Keywords: self-regulation strategies; teaching self-efficacy; practicum course; Education & Educational Research